TEACHING SCIENCE FOR UNDERSTANDING: THE PROJECT-BASED APPROACH - Said, Suwaiba Ahmad (Sokoto Educational Review, 2018)
The paper focuses on project-based approach generally which is an approach that relies on the notion that learners learn better and more meaningful if given opportunity to participate in a project and from their experiences. Projects-based instruction was discussed. Project based learning was also examined. The paper concluded by identifying conditions that can affect effective utilization or hinder the project-based approach.